1992
DOI: 10.1128/mcb.12.9.3865
|View full text |Cite
|
Sign up to set email alerts
|

NSR1 is required for pre-rRNA processing and for the proper maintenance of steady-state levels of ribosomal subunits.

Abstract: NSR1 is a yeast nuclear localization sequence-binding protein showing striking similarity in its domain structure to nucleolin. Cells lacking NSR1 are viable but have a severe growth defect. We show here that NSR1, like nucleolin, is involved in ribosome biogenesis. The nsrl mutant is deficient in pre-rRNA processing such that the initial 35S pre-rRNA processing is blocked and 20S pre-rRNA is nearly absent. The reduced amount of 20S pre-rRNA leads to a shortage of 18S rRNA and is reflected in a change in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
104
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 24 publications
6
104
0
Order By: Relevance
“…These data suggest that Nopp52, nucleolin, and NSR1 are members of a protein family with potentially related functions. However, nucleolin does not rescue the slow growth phenotype of yeast NSR1 mutants (Lee et al, 1992) and, therefore, complete functional identity cannot be assumed from structural similarities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that Nopp52, nucleolin, and NSR1 are members of a protein family with potentially related functions. However, nucleolin does not rescue the slow growth phenotype of yeast NSR1 mutants (Lee et al, 1992) and, therefore, complete functional identity cannot be assumed from structural similarities.…”
Section: Discussionmentioning
confidence: 99%
“…Both nucleolin and NSR1 appear to be involved in prerRNA processing. In yeast NSR1 mutants, there is a disruption of pre-rRNA processing (Kondo and Inouye, 1992;Lee et al, 1992). Nucleolin is associated with pre-rRNA (Herrera and Olson, 1986) and this association appears to involve both the RRMs and the GRF-rich regions (Sapp et al, 1989;Ghisolfi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of genes encoding nucleolin homologue in budding (NSR1) and fission (GAR2) yeast produce severe effects on cell growth and disrupt balanced production of the small and large ribosomal subunits (Lee et al, 1992;Gulli et al, 1995). Moreover, it has been shown that the nucleolar structure in gar2 cells is dramatically reorganized and unusual structures are detected (Leger-Silvestre et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Striking changes in the levels of 60S subunits have been observed in strains having a mutation in either the SPB4 or RRP1 gene, whose products are involved in processing of the 27S precursor to the mature 25S rRNA (1,45). Strains bearing a null allele of NSR1 were shown to have defects in processing of the 20S rRNA precursor to 18S rRNA as well as changes in the steady-state level or distribution of 40S ribosomal subunits (28). Mutations in two genes encoding translation factors, GCD2 (14), and SUII (67), affect steady-state levels of 80S monoribosomes and polyribosomes.…”
mentioning
confidence: 99%